1987
DOI: 10.1093/schbul/13.2.241
|View full text |Cite
|
Sign up to set email alerts
|

The Disorder of Consciousness in Schizophrenia

Abstract: The schizophrenic experience is described as an inability to sustain an intentional focus to attention. Attention is captured by incidental details in the schizophrenic patient's environment, and this gives rise to a spurious sense of significance. The patient's inability to direct a train of thought prevents full access to long-term memory so that early components of perception, which are designed to give early warning of threat, are overly influential and unmodulated by further mental processing. These hasty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(55 citation statements)
references
References 107 publications
3
51
0
Order By: Relevance
“…To begin with, the consensus opinion that schizophrenia represents a disorder of attention (e.g., Anscombe, 1987;Braff, 1993;Mirsky & Duncan, 1986;Nuechterlein & Dawson, 1984) requires a confirmation that LI, at least in part, is indeed governed by such processes. This position gains support from experiments that demonstrate that generating LI in adult humans requires a masking task in the preexposure stage, and that LI is modulated by the difficulty (load) of the masking task.…”
Section: Theoretical Issues For Latent Inhibition and Their Implicatimentioning
confidence: 99%
“…To begin with, the consensus opinion that schizophrenia represents a disorder of attention (e.g., Anscombe, 1987;Braff, 1993;Mirsky & Duncan, 1986;Nuechterlein & Dawson, 1984) requires a confirmation that LI, at least in part, is indeed governed by such processes. This position gains support from experiments that demonstrate that generating LI in adult humans requires a masking task in the preexposure stage, and that LI is modulated by the difficulty (load) of the masking task.…”
Section: Theoretical Issues For Latent Inhibition and Their Implicatimentioning
confidence: 99%
“…However, current research is clearly not restricted to this domain, and the presumed abnormality is claimed to underlie a much wider range of behaviours and experiences characteristic of schizophrenia. Thus, Anscombe (1987) argued that "perceptions are not placed in a context of background knowledge" (p. 256). In similar vein, Hemsley (1994) suggested that it is a failure of context to activate appropriate schema to guide processing that is crucial to the emergence of some forms of delusional beliefs.…”
Section: Commentary/phillipsmentioning
confidence: 99%
“…A part from these symptoms, schizophrenic patients also display a number of attentional impairments, which have already been described by Bleuler in 1911. It is assumed that the underlying neural m echanism s and brain structures involved in this im pairm ent are representative for the disorder in general (Anscombe 1987;Frith 1992). Moreover, these attentional impairments have been used to model (aspects) of schizophrenia in animals (Ellenbroek and Cools 1990;Weiner 1991, 1992).…”
Section: Introductionmentioning
confidence: 97%